CuKMoS2 / SiO2 catalyst for synergistically preparing methyl mercaptan from carbon dioxide and hydrogen sulfide
By introducing a small amount of copper (Cu) into the KMoS2/SiO2 catalyst, the CuKMoS2/SiO2 catalyst was formed, and the problems of low activity and poor selectivity of existing MoS2 catalysts were solved, which significantly improved the selectivity of methanethiol formation and reaction efficiency.
Patent Information
- Application Number
- CN202510002502.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing MoS2 catalysts have low activity and poor selectivity in the coordinated catalytic reaction of carbon dioxide and hydrogen sulfide, especially in controlling the formation of methanol in the intermediate product.
By introducing a small amount of copper (Cu) into the KMoS2/SiO2 catalyst, the incorporation ratio and vulcanization process of Cu and K are optimized to form CuKMoS2/SiO2 catalyst, which significantly improves the selectivity of the catalyst for methanol intermediates, thereby improving the selectivity of methanethiol formation.
It significantly improves the selectivity of methylmercaptan production and reduces the generation of by-products, especially unnecessary by-products such as methane, providing a new and efficient catalytic material for the green synthesis of methylmercaptan.
Smart Images

Figure CN119733533A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation technology of an environmental catalyst and its application field, and in particular to a preparation method of a CuKMo / SiO2 catalyst for synergistically preparing methyl mercaptan from carbon dioxide and hydrogen sulfide and its application. Background Art
[0002] Carbon dioxide (CO2) and hydrogen sulfide (H2S) are common byproducts in industrial processes. CO2 is a greenhouse gas, and excessive emissions can cause global warming, while H2S is highly corrosive and toxic and must be strictly treated before it can be discharged. Therefore, how to effectively utilize CO2 and H2S is an important research direction in the current field of environmental protection and resource utilization.
[0003] Methyl mercaptan (CH3SH) is an important chemical raw material, widely used in organic synthesis, pesticides, medicines and rubber. Traditionally, the industrial production of methyl mercaptan mostly relies on the reaction of methanol and hydrogen sulfide (H2S) in the presence of an acidic catalyst. However, with the increasing requirements for environmental protection and the sustainable use of resources, more and more research in recent years has focused on the development of green catalytic systems for the production of methyl mercaptan using carbon monoxide (CO) and hydrogen sulfide as raw materials. If carbon dioxide CO2 and H2S can be converted into high-value-added chemicals, it will not only reduce greenhouse gas emissions, but also make full use of sulfur-containing waste gas resources, which has great environmental and economic significance.
[0004] In previous studies on the synergistic catalytic reaction of CO and H2S, molybdenum sulfide (MoS2) and its derivative catalysts have become one of the main catalyst materials for this type of reaction due to their unique layered structure and good sulfur affinity. However, a single MoS2 catalyst has problems of low activity and poor selectivity in actual reactions, especially in controlling the generation of intermediates such as methanol (CH3OH), which makes it difficult to achieve the desired effect. In addition, the long-term stability of MoS2 catalysts also presents certain challenges. Therefore, how to optimize the composition and structure of MoS2 catalysts to improve their activity and selectivity has become a research focus in this field.
[0005] The present invention develops a CuKMoS2 / SiO2 catalyst for the synergistic preparation of methyl mercaptan from carbon dioxide and hydrogen sulfide. By optimizing the doping ratio of Cu and K and the sulfidation process, the selectivity of the catalyst for methanol intermediates is significantly improved, thereby improving the formation selectivity of methyl mercaptan and effectively inhibiting the formation of by-products, providing a new and efficient catalytic material for the green synthesis of methyl mercaptan. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of CuKMoS2 / SiO2 for the synergistic preparation of methyl mercaptan from carbon dioxide and hydrogen sulfide in view of the deficiencies of the prior art. Adding a small amount of Cu to the KMoS2 / SiO2 catalyst can effectively adsorb and dissociate the reactants H2 and H2S, and induce the reaction to generate an important intermediate product, methanol, thereby greatly improving the selectivity for methyl mercaptan.
[0007] To achieve the above object, the present invention is implemented by the following technical solutions: A method for preparing a CuKMoS2 / SiO2 catalyst comprises the following steps: (1) Mix Cu(NO3)2·3H2O and K2MoO4 and add a small amount of water for preliminary wetting; (2) grinding the mixture obtained in step (1) under a warming lamp, and gradually adding citric acid aqueous solution during the grinding process; (3) adding a SiO2 carrier to the solution obtained in step (2), stirring at 80° C. to allow the metal ions to be evenly impregnated into the carrier; (4) drying the impregnated sample and calcining it under N2 atmosphere to promote the decomposition and fixation of the precursor; (5) Sulfurization in H2S atmosphere to form MoS2 structure and introduce sulfur element into the catalyst to finally form CuKMoS2 / SiO2 catalyst.
[0008] Preferably, the molar ratio of Mo to Cu in step (1) is 1:0.01 to 1:0.5, preferably 1:0.05.
[0009] Preferably, the grinding time in step (2) does not exceed 20 minutes, preferably 15 minutes.
[0010] Preferably, the concentration of the citric acid aqueous solution in step (2) does not exceed 25 wt %.
[0011] Preferably, the amount of citric acid added in step (2) is 1.74 mmol.
[0012] Preferably, in step (3), the loading amount of Mo on the carrier (calculated as MoO3) is 5wt% to 30wt%, preferably 20wt%.
[0013] Preferably, the stirring rate in step (3) is 300 r / min.
[0014] Preferably, the calcination temperature in step (4) is 300-500°C, preferably 450°C.
[0015] Preferably, the volume concentration of sulfide gas in step (5) is H2S / H2=5%~90%, preferably 10%.
[0016] Preferably, the vulcanization temperature in step (5) is 250-700°C.
[0017] Preferably, the vulcanization temperature in step (5) is 250°C for in-situ vulcanization for 4 hours, and then increased to 350°C for further vulcanization for 4 hours.
[0018] Preferably, the final product is CuKMoS2 / SiO2.
[0019] Application: Application of CuKMoS2 / SiO2 catalyst in the synergistic preparation of methyl mercaptan from carbon dioxide and hydrogen sulfide: The reaction temperature for the synergistic preparation of methyl mercaptan from H2S and CO2 is 200~500°C, and the reaction pressure is 0.5~1.8 MPa. Preferably, the reaction temperature is 320°C and the reaction pressure is 1.5MPa.
[0020] Preferably, the amount of the CuKMoS2 / SiO2 catalyst is 1 g; the volume concentration of H2S is 4%, the volume concentration of CO2 is 1%, the volume concentration of H2 is 4%, and N2 is the balance gas.
[0021] The present invention has the following advantages and beneficial effects: 1. The present invention significantly improves the selectivity of the catalyst for the reaction intermediate methanol (CH3OH) by introducing a small amount of copper (Cu) into the KMoS2 / SiO2 catalyst, thereby enhancing the generation selectivity of methyl mercaptan (CH3SH). Compared with the KMoS2 / SiO2 catalyst, the catalyst of the present invention can more effectively promote the generation of the target product methyl mercaptan under the same conditions, while reducing the generation of by-products, especially unnecessary by-products such as methane (CH4).
[0022] 2. By grinding the precursors of Mo and Cu under a warming lamp, Cu can be effectively bonded to the structure of Mo and the dispersion of Cu can be promoted, so that a small amount of Cu addition can obtain high catalytic reaction activity.
[0023] 3. The introduction of copper (Cu) not only promotes the electron transfer of the active center, but also regulates the reaction path of CO2 and H2S, making the reaction more inclined to produce methyl mercaptan.
[0024] 4. The catalyst preparation method of the present invention is simple, and the loading of Cu, K, and MoS2 active components can be achieved through conventional impregnation and sulfurization processes. The process is repeatable, suitable for industrial large-scale production, and has low cost and good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1X-ray powder diffraction spectra of the catalysts prepared in Examples 1, 2, 3 of the present invention and Comparative Examples 1 and 2; Figure 2 The EPR diagrams of the catalysts prepared in Examples 1, 2, 3 of the present invention and Comparative Examples 1 and 2; Figure 3 TEM and mapping images of 0.05CuKMo / SiO2 prepared in Example 1 of the present invention; Figure 4 TEM image of Example 1 of the present invention; Figure 5 N2 adsorption isotherm curves of Example 1 and Comparative Example 1 of the present invention; Figure 6 1 is a pore size distribution diagram of Example 1 of the present invention and Comparative Example 1; Figure 7 This is the Cu LMMXPS characterization of Example 1 of the present invention; Figure 8 The Mo 3d XPS characterization of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in detail below in conjunction with embodiments and drawings. The examples described are further explanations of the present invention rather than limitations of the contents of the present invention.
[0027] Example 1 A preparation method of CuKMoS2 / SiO2: 1.74 mmol potassium molybdate and 0.085 mmol copper nitrate are weighed and mixed, and water equal to the volume of the powder is added for preliminary wetting, and the mixture is ground under a warm baking lamp, and 5 mL of an aqueous solution containing 1.74 mmol citric acid is slowly added during the grinding process. After grinding for 15 minutes, the mixed solution is transferred to a beaker, and 1 g of SiO2 carrier is added, and stirred at 300 r / min at 80 ° C until slightly dry. After drying at 80 ° C for 12 h, the sample is placed in a muffle furnace and calcined at 400 ° C for 3 h in a N2 atmosphere, and the product between 40 and 60 meshes is sieved after cooling to room temperature. In the reaction gas (10% H2S / H2 mixed gas), it is in-situ sulfurized at 250 ° C for 4 h, and then the temperature is raised to 350 ° C for further sulfurization for 4 h to obtain the final product named 0.05CuKMo / SiO2.
[0028] Example 2 A preparation method of CuKMoS2 / SiO2: 1.74 mmol potassium molybdate and 0.1275 mmol copper nitrate are weighed, and water equal to the volume of the powder is added for preliminary wetting, and the mixture is ground under a warm baking lamp, and 5 mL of an aqueous solution containing 1.74 mmol citric acid is slowly added during the grinding process. After grinding for 15 minutes, the mixed solution is transferred to a beaker, and 1 g of SiO2 carrier is added, and stirred at 300 r / min at 80 ° C until slightly dry. After drying at 80 ° C for 12 h, the sample is placed in a muffle furnace and calcined at 400 ° C for 3 h, and the product between 40 and 60 meshes is sieved after cooling to room temperature. In the reaction gas (10% H2S / H2 mixed gas), it is in-situ sulfurized at 250 ° C for 4 h, and then the temperature is raised to 350 ° C for further sulfurization for 4 h, and the final product is named 0.075CuKMo / SiO2.
[0029] Example 3 A preparation method of CuKMoS2 / SiO2: 1.74 mmol potassium molybdate and 0.0425 mmol copper nitrate are weighed, and water equal to the volume of the powder is added for preliminary wetting, and the mixture is ground under a warm baking lamp, and 5 mL of an aqueous solution containing 1.74 mmol citric acid is slowly added during the grinding process. After grinding for 15 minutes, the mixed solution is transferred to a beaker, and 1 g of SiO2 carrier is added, and the mixture is stirred at 300 r / min at 80°C until slightly dry, and the sample is placed in a muffle furnace and calcined at 400°C for 3 hours after drying at 80°C for 12 hours, and the product between 40 and 60 meshes is sieved after cooling to room temperature. The mixture is in-situ sulfurized at 250°C for 4 hours in a reaction gas (10% H2S / H2 mixed gas), and then the mixture is heated to 350°C and sulfurized for 4 hours to obtain the final product named 0.025CuKMo / SiO2.
[0030] Comparative Example 1 (no Cu added) A K2MoS x Preparation method of KMo / SiO2: Weigh 1.74 mmol potassium molybdate and drip water equal to the volume of the powder for preliminary wetting. Grind under a warm lamp and slowly drip 5 mL of an aqueous solution containing 1.74 mmol citric acid during the grinding process. After grinding for 15 minutes, transfer the mixed solution to a beaker and add 1 g of SiO2 carrier. Stir at 80 °C at 300 r / min until slightly dry. After drying at 80 °C for 12 h, place the sample in a muffle furnace and roast at 400 °C for 3 h. After cooling to room temperature, sieve out the product between 40 and 60 mesh. In the reaction gas (10% H2S / H2 mixed gas), in-situ sulfurization was performed at 250 °C for 4 h, and then the temperature was raised to 350 °C for further sulfurization for 4 h. The final product was named KMo / SiO2.
[0031] Comparative Example 2 (without addition of Cu and K) A MoS x Preparation method of / SiO2: Weigh 1.49 mmol of ammonium molybdate and grind it under a warm lamp, and add water of the same volume as the powder for preliminary wetting, and slowly add 5 mL of an aqueous solution containing 1.74 mmol of citric acid during the grinding process. After grinding for 15 minutes, transfer the mixed solution to a beaker, add 1 g of SiO2 carrier, and stir at 300 r / min at 80 °C until slightly dry. After drying at 80 °C for 12 h, place the sample in a muffle furnace and roast it at 400 °C for 3 h. After cooling to room temperature, sieve out the product between 40 and 60 meshes. In the reaction gas (10% H2S / H2 mixed gas), in-situ sulfurization is carried out at 250 °C for 4 h, and then the temperature is raised to 350 °C for further sulfurization for 4 h. The final product is named Mo / SiO2.
[0032] Application Experiment 1g of catalyst was loaded into a fixed bed reactor, and the reaction pressure was set to 1.5 MPa and the total space velocity was set to 300 GHSV. The device was started, the temperature was raised to the target reaction temperature and the system was stabilized. A reaction gas of 4% H2S / 1% CO2 / 4% H2 / N2 was introduced by volume percentage. The reaction product was condensed and analyzed by online gas chromatography for the yield and selectivity of methyl mercaptan, and the formation of intermediate products such as methanol was monitored at the same time.
[0033] X-ray powder diffraction (XRD): The phase characterization of the samples was measured using the X'pert pro powder diffractometer from Panalytical, with an X'celerator as the detector, a copper target (Cu Kα, λ = 0.154 nm) as the excitation radiation source, an operating voltage of 45 KV, and an operating current of 40 mA.
[0034] N2 physisisorption: The specific surface area and pore size distribution of the sample were determined by N2 physisisorption. The instrument was a 3Flex fully automatic analyzer produced by Micrometric, USA. The test conditions were as follows: 0.15 g of sample was weighed, pre-treated and degassed at 250 °C for 4 hours, cooled to room temperature, and the texture information of the sample was obtained by static adsorption in a cold trap cooled to -196 °C by liquid nitrogen. The specific surface area and pore size distribution of the sample were calculated according to the BET equation and the BJH model, respectively.
[0035] Electron Paramagnetic Resonance: Information about sample defects or oxygen vacancies can be obtained using an E-500 electron paramagnetic resonance instrument (Bruker). The test is conducted at room temperature with a test frequency of 100 kHz. After the sample is placed in a quartz tube, the tube must be kept vertical and the instrument's working environment must be stable and air ventilated.
[0036] Scanning electron microscopy (SEM): The morphology of the catalyst was observed using a S-4800 field emission scanning electron microscope. The vacuum degree of the analysis chamber was less than 2.7×10 –6 Pa, the scanning voltage and current were 5 kV and 7 μA respectively. The sample powder was glued to the conductive glue and then observed after gold spraying.
[0037] X-ray photoelectron spectroscopy (XPS): EscaLab 250Xi spectrometer was used to analyze the elemental composition and chemical state of the catalyst surface. The excitation light source was Al target Kα ray, and the vacuum degree of the analysis chamber was <10 –8 bar, the excitation power was 22.5 W, and the binding energy of C1s at 284.8 eV was used for calibration.
[0038] Field emission transmission electron microscopy (TEM): TEM images of the samples were observed on a JEM-F200 transmission electron microscope (TEM) with an accelerating voltage of 200 KV.
[0039] Figure 1 The XRD diagrams of Examples 1, 2, and 3 of the present invention and Comparative Examples 1 and 2 show that the peak of 1T-MoS2 is located near 9°. The incorporation of K is beneficial to the formation of 1T-MoS2, and with the addition of Cu, the peak attributable to Cu appears. 0.67 6S 0.95 The peaks indicate that there is a bond between Cu and MoS2, and it is not a simple free state. As the amount of Cu added increases, the aggregation of K2SO4 in the catalyst becomes more obvious, indicating that excessive Cu addition may have an adverse effect on the catalytic effect.
[0040] Figure 2 The EPR graphs of Examples 1, 2, 3 of the present invention and Comparative Examples 1 and 2 show that, as the amount of Cu added increases, the sulfur vacancies of the catalyst first increase and then decrease. Combined with the XRD characterization, it can be inferred that the K2SO4 on the surface covers the catalytic active sites, which is not conducive to the sulfurization of the catalyst.
[0041] Figure 3TEM and mapping images of 0.05CuKMo / SiO2 prepared in Example 1 of the present invention. It can be observed from the figure that Cu and Mo are partially deposited on the surface of the carrier, but most of them still penetrate into the pores of the carrier and are dispersed relatively evenly.
[0042] Figure 4 This is the TEM image of Example 1 of the present invention. It can be seen from the figure that MoS2 has multiple crystal planes, and the molybdenum disulfide prepared by this method can expose more active sites.
[0043] Figure 5 The N2 adsorption isotherms of Example 1 and Comparative Example 1 of the present invention are both type IV isotherms.
[0044] Figure 6 The pore size distribution diagrams of Example 1 and Comparative Example 1 of the present invention show that the particle size of the samples is more uniform after Cu is added.
[0045] Figure 7 The Cu LMMXPS characterization of Example 1 of the present invention shows that Cu exists in two forms: 0-valent and 1-valent. 0 Can adsorb and dissociate H2, Cu + It can stabilize the reaction intermediate methoxy group.
[0046] Figure 8 The Mo 3d XPS characterization of Example 1 and Comparative Example 1 of the present invention shows that Mo 6+ The peak of is obviously lowered, indicating that Cu doping can effectively induce the sulfidation of Mo.
[0047] Table 1 and Table 2 are the data of the reactant CO2 conversion rate and product CH3SH selectivity of the catalysts of Examples 1, 2, 3 of the present invention and Comparative Examples 1 and 2 under different reaction temperature conditions. In the reaction of CO2 and H2S synergistically preparing CH3SH, the CO2 conversion rate of all catalysts increases with the increase of reaction temperature. It can be seen from Tables 1 and 2 that when the reaction temperature is 320 ° C, the methyl mercaptan selectivity of Example 1 is the highest, which is 90.1%; when the reaction temperature is 320 ° C, the methyl mercaptan selectivity of Example 2 is the highest, which is 86.4%; the selectivity of all embodiments is better than that of Comparative Example 1, that is, the Cu-doped KMoS2 / SiO2 designed by the present invention has better performance.
[0048] Table 1 Table 2 The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a CuKMoS2 / SiO2 catalyst for synergistically preparing methyl mercaptan from carbon dioxide and hydrogen sulfide, characterized in that: The following steps are involved: (1) Mix Cu(NO3)2·3H2O and K2MoO4 and add a small amount of water for preliminary wetting; (2) grinding the mixture obtained in step (1) under a warming lamp, and gradually adding a citric acid aqueous solution dropwise during the grinding process; (3) adding a SiO2 carrier to the solution obtained in step (2), stirring at 80°C to allow the metal ions to be evenly impregnated onto the carrier; (4) Drying the impregnated sample and calcining it under N2 atmosphere to promote the decomposition and fixation of the precursor; (5) Sulfurization in H2S atmosphere to form MoS2 structure, and introduce sulfur element into the catalyst to finally form CuKMoS2 / SiO2 catalyst.
2. The preparation method according to claim 1, characterized in that: The molar ratio of Mo to Cu in step (1) is 1:0.01 to 1:0.
5.
3. The preparation method according to claim 1, characterized in that: The concentration of the citric acid aqueous solution in step (2) does not exceed 25 wt %.
4. The preparation method according to claim 1, characterized in that: The grinding time in step (2) does not exceed 20 minutes.
5. The preparation method according to claim 1, characterized in that: In step (3), the loading amount of Mo on the carrier is 5wt%~30wt% calculated as MoO3.
6. The preparation method according to claim 1, characterized in that: The calcination temperature in step (4) is 300-500°C.
7. The preparation method according to claim 1, characterized in that: The concentration of sulfide gas in step (5) is H2S / H2=5%~90%.
8. The preparation method according to claim 1, characterized in that: The vulcanization temperature in step (5) is 250-700°C.
9. A CuKMoS2 / SiO2 catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the CuKMoS2 / SiO2 catalyst according to claim 9 in the synergistic preparation of methyl mercaptan by carbon dioxide and hydrogen sulfide, characterized in that: When H2S and CO2 are used to synergistically prepare methyl mercaptan, the volume ratio of the components in the raw gas is H2:H2S:CO2=4:4:1, the reaction temperature is 200~500 ℃, and the reaction pressure is 0.5~1.8 MPa.
Citation Information
Patent Citations
Supported Mo-O-K-MexOy catalyst for synthesizing methyl hydrosulfide from high H2S synthesis gas
CN101468310A
Process for continuously preparing methyl mercaptan from carbon- and hydrogen-containing compounds
CN101743221A
Method for the continuous production of methyl mercaptan from carbon-containing compounds, sulfur, and hydrogen
CN102548961A
K insertion type 1T-MoS2 catalyst as well as preparation method and application thereof
CN112316959A
Preparation method of reaction catalyst for preparing methyl mercaptan through synergism of hydrogen sulfide and carbon dioxide and application of reaction catalyst
CN117364124A
Cited By
Preparation method and preparation device of mercaptan
CN121202739A
Process for preparing mercaptans and apparatus therefor
CN121202739B